Serve speed peaks in FIVB world tour beach volleyball (2005-2012) - Palao, J. M.; Palades, D. (Acta Kinesiologica, 2014)
The purpose of this study was to give reference values for serve speed peaks. A retrospective analysis of the 10-20 fastest serves in men´s and women´s World Tour beach volleyball from the 2005 to the 2012 seasons was done. A total of 136 serves from the men´s competition and 141 serves from the women's competition was included in the study. The results show: 1) for males, the average serve speed peak was 98.3 ± 4.3 km·h-1, and the serve speed peak was 114.0 km·h-1; and 2) for females, the average serve speed peak found was 80.0 ± 2.7 km·h-1 and the serve speed peak was 86.5 km·h-1. No significant differences were found between the first four years and the next four years in the men´s competition, there were significant differences between the first four years and the second four years in the women´s competition. Significant differences were found between men and women in speed serve peaks. The data found can help coaches establish the reference values of serve speed for the power serve to assist in working on the serve and reception in training.